Terminal complement complex deposition on chondrocytes promotes premature senescence in age- and trauma-related osteoarthritis - Ruths, Leonie; Hengge, Jana; Teixeira, Graciosa Q.; Haffner-Luntzer, Melanie; Ignatius, Anita; Riegger, Jana (Frontiers in Immunology, 2025)
BackgroundThe complement system is locally activated after joint injuries and leads to the deposition of the terminal complement complex (TCC). Sublytic TCC deposition is associated with phenotypical alterations of human articular chondrocytes (hAC) and enhanced release of inflammatory cytokines. Chronic inflammation is a known driver of chondrosenescence in osteoarthritis (OA). Therefore, we investigated whether TCC deposition contributes to stress-induced premature senescence (SIPS) during aging in vivo and after ex vivo cartilage injury.MethodsFemoral condyles of male 13-week-old and 72-week-old CD59-ko (higher TCC deposition), C6-deficient (insufficient TCC formation), and C57BL/6 (WT) mice were collected to assess age-related OA. Furthermore, macroscopically intact human and porcine cartilage explants were traumatized and cultured with/without 30% human serum (HS) to activate the complement system. Explants were additionally treated with clusterin (CLU, TCC inhibitor), N-acetylcysteine (NAC, antioxidant), Sarilumab (IL-6 receptor inhibitor), STAT3-IN-1 (STAT3 inhibitor), or IL-1 receptor antagonist (IL-1RA) in order to investigate the consequences of TCC deposition. Gene and protein expression of senescence-associated markers such as CDKN1A and CDKN2A was determined.ResultsIn the murine aging model, CD59-ko mice developed after 72 weeks more severe OA compared to C6-deficient and WT mice. mRNA analysis revealed that the expression of Cdkn1a, Cdkn2a, Tp53, Il1b, and Il6 was significantly increased in the cartilage of CD59-ko mice. In human cartilage, trauma and subsequent stimulation with HS increased mRNA levels of CDKN1A, CDKN2A, and IL6, while inhibition of TCC formation by CLU reduced the expression. Antioxidative therapy with NAC had no anti-senescent effect. In porcine tissue, HS exposure and trauma had additive effects on the number of CDKN2A-positive cells, while Sarilumab, STAT-IN-1, and IL-1RA reduced CDKN2A expression by trend.ConclusionOur results demonstrate that complement activation and consequent TCC deposition is associated with chondrosenescence in age-related and trauma-induced OA. We provided evidence that the SIPS-like phenotype is more likely induced by TCC-mediated cytokine release rather than oxidative stress. Overall, targeting TCC formation could be a future approach to attenuate OA progression.